2023
DOI: 10.26508/lsa.202201810
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of Rab1A in secretion and autophagy: hypervariable domain dependence

Abstract: We currently understand how the different intracellular pathways, secretion, endocytosis, and autophagy are regulated by small GTPases. In contrast, it is unclear how these pathways are coordinated to ensure efficient cellular response to stress. Rab GTPases localize to specific organelles through their hypervariable domain (HVD) to regulate discrete steps of individual pathways. Here, we explored the dual role of Rab1A/B (92% identity) in secretion and autophagy. We show that although either Rab1A or Rab1B is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Data indicating the fifth helix and the hyper variable domain tail of Rabs are important for their specificity and localization is emerging 30,68,69 . Gyurkovska et al recently showed despite Rab1A and Rab1B sharing 92% amino acid similarity, only Rab1A is required for stress-induced autophagy 29 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Data indicating the fifth helix and the hyper variable domain tail of Rabs are important for their specificity and localization is emerging 30,68,69 . Gyurkovska et al recently showed despite Rab1A and Rab1B sharing 92% amino acid similarity, only Rab1A is required for stress-induced autophagy 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Rab dysfunction interferes with the proper recruitment of these Golgi related proteins and results in disintegration 73 . In fact, disruption of Rab1B homeostasis, or inactivation of just Rab1A or Rab1B in tissue culture cells affects Golgi stability and leads to its fragmentation 19,29,35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations